Bioanalytical Method Validation of an RP-HPLC Method for Determination of Rifampicin in Liver Perfusion Studies - Izat, Nihan; Kaplan, Ozan; Celebier, Mustafa; Sahin, Selma (Current Pharmaceutical Analysis, 2021)
Background: The number of validated quantification methods for rifampicin, a prototypical Oatp inhibitor, in biological rat samples is limited. Objective: This study was conducted to validate a modified reversed-phase liquid chromatographic method for the determination of rifampicin in rat liver tissue according to the current ICH M10 Bioanalytical Method Validation Draft Guideline (2019) for application to samples of in situ rat liver perfusion studies. Methods: Liver tissue samples were obtained from recirculatory in situ rat liver perfusion studies. The analysis was performed on a C18 column with a mobile phase composed of 0.05 M phosphate buffer (pH 4.58): acetonitrile (55:45, v/v). The assay was validated for selectivity, calibration curve and range, matrix effect, carry-over, accuracy and precision, reinjection reproducibility, and stability. Results: The method was considered selective and stable, without having carry-over and matrix effects. The calibration curve was linear (R2: 0.9983) within the calibration range (0.5-60 ppm). Accuracy and precision values fulfilled the required limits. Liver concentrations of rifampicin in liver tissue, obtained after 60 min perfusion with 10 μM and 50 μM of rifampicin, were 45.1 ± 11.2 and 313.4 ± 84.4 μM, respectively. Conclusion: The bioanalytical method validation was completed and the method was successfully applied for the determination of rifampicin in rat liver tissue.
Keywords: OATP